Simultaneous Search and Network Efficiency - Pieter A. Gautier; Christian Holzner (Center for Economic Studies and ifo Institute (CESifo), 2011)
When workers send applications to vacancies they create a network. Frictions arise if workers do not know where other workers apply to (this affects network creation) and firms do not know which candidates other firms consider (this affects network clearing). We show that those frictions and the wage mechanism are in general not independent. Equilibria that exhibit wage dispersion is inefficient in terms of network formation. Under complete recall (firms can go back and forth between all their candidates) only wage mechanisms that allow for ex post Bertrand competition generate the maximum matching on a realized network.
Keywords: D83; D85; E24; J64; 330; efficiency; network clearing; random bipartite network formation; simultaneous search; Arbeitsplatzsuchmodell; Arbeitsnachfrage; Netzwerk; Lohn; Matching; Arbeitsmarkt; Markteffizienz; Theorie